Checklist of Angiosperms extant in Mirpur area of Dhaka city (Jahangirnagar University Journal of Biological Sciences, 2018)
This study has recognized the occurance of a total of 346 species of Angiosperms under 256 genera and 82 families and assessed their current status and distribution in Mirpur area of Dhaka district. Majority of these families, 68 (82.92%) consist of 255 species under 192 genera, belong to Magnoliopsida (dicotyledons), and the rest 14 (17.07%) comprise of 91 species under 64 genera to Liliopsida (monocotyledons). Asteraceae with 18 species is found to be the largest family in Magnoliopsida followed by Euphorbiaceae and Fabaceae consists of 17 species each; while Poaceae is recognized as the largest family with 41 species in Liliopsida followed by Cyperaceae with 19 species. Ficus of Moraceae and Cyperus of Cyperaceae, each consists of 6 species, are found to be the largest genera in Magnoliopsida and Liliopsida, respectively. Total 236 species have been recorded as herbs followed by 58 tree seedlings, 50 shrubs and 2 lianas. Scrub jungles harbouring a total of 90 species are found to be the most common habitat of Angiosperms in the area, which is followed by marginal lands, road sides, grasslands, lake banks, fallow lands, woodlands, river bank, and highland slope and wet lands. A total of 281 economically important species have been determined from the study area. The occurrence of two threatened species, viz. Andrographis paniculata (Burm.f.) Nees and Rauvolfia serpentina (L.) Benth. ex Kurz, listed in the Red Data Book of Bangladesh, is recognized to be Vulnerable (V) in the study area.Jahangirnagar University J. Biol. Sci. 7(2): 47-64, 2018 (December)